Hepatic Venous Outflow Obstruction: Suggestion of a New Classification - Santosh Man Shrestha (Journal of Renal and Hepatic Disorders, 2017)
Hepatic venous outflow obstruction (HVOO) is common in developing countries. It is a serious condition that clinically manifests with ascites from sinusoidal hypertension, and carries the risk of high mortality or development of liver cirrhosis. In the past, the eponym Budd–Chiari Syndrome (BCS) was used synonymously for HVOO. In the West, hepatic vein (HV) thrombosis caused by prothrombotic disorders is the main cause of HVOO. In the East, obliterative disease of hepatic portion of inferior vena cava induced by bacterial infection, now renamed hepatic vena cava syndrome, is the common cause of HVOO. These two diseases with different etiology, epidemiology, and natural history are at present grouped together under BCS causing much confusion. Sinusoidal obstruction syndrome, another important cause of HVOO at the level of the sinusoid and terminal HV, was left out in the classification of HVOO. In this article, the pathophysiology of sinusoidal hypertension is described, the term BCS is redefined, and a new classification of HVOO is suggested.